Modern Morphometrics in Physical Anthropology - Slice, Dennis E.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
Morphometrics has undergone a revolutionary transformation in the past two decades as new methods have been developed to address shortcomings in the traditional multivirate analysis of linear distances, angles, and indices. While there is much active research in the field, the new approaches to shape analysis are already making significant and ever-increasing contributions to biological research, including physical anthropology. Modern Morphometrics in Physical Anthropology highlights the basic machinery of the most important methods, while introducing novel extensions to these methods and illustrating how they provide enhanced results compared to more traditional approaches. Modern Morphometrics in Physical Anthropology provides a comprehensive sampling of the applications of modern, sophisticated methods of shape analysis in anthropology, and serves as a starting point for the exploration of these practices by students and researchers who might otherwise lack the local expertise or training to get started. This text is an important resource for the general morphometric community that includes ecologists, evolutionary biologists, systematists, and medical researchers.
A glossary for morphometrics -- Modern Morphometrics -- Theory and Methods -- After Landmarks -- Semilandmarks in Three Dimensions -- An Alternative Approach to Space Curve Analysis Using the Example of the Neanderthal Occipital Bun -- Correcting for the Effect of Orientation in Geometric Morphometric Studies of Side-View Images of Human Heads -- Fourier Descriptors, Procrustes Superimposition, and Data Dimensionality: An Example of Cranial Shape Analysis in Modern Human Populations -- Problems with Landmark-Based Morphometrics for Fractal Outlines: The Case of Frontal Sinus Ontogeny -- An Invariant Approach to the Study of Fluctuating Asymmetry: Developmental Instability in a Mouse Model for Down Syndrome -- Applications -- Comparison of Coordinate and Craniometric Data for Biological Distance Studies -- Assessing Craniofacial Secular Change in American Blacks and Whites Using Geometric Morphometry -- Secular Trends in Craniofacial Asymmetry Studied by Geometric Morphometry and Generalized Procrustes Methods -- The Morphological Integration of the Hominoid Skull: A Partial Least Squares and PC Analysis with Implications for European Middle Pleistocene Mandibular Variation -- A Geometric Morphometric Analysis of Late Pleistocene Human Metacarpal 1 Base Shape -- A Geometric Morphometric Assessment of the Relationship between Scapular Variation and Locomotion in African Apes -- Functional Shape Variation in the Cercopithecine Masticatory Complex -- A Geometric Morphometric Assessment of the Hominoid Supraorbital Region: Affinities of the Eurasian Miocene Hominoids Dryopithecus, Graecopithecus, and Sivapithecus.
Keywords: Social sciences; Ecology; Evolutionary biology; Anthropology; Social Sciences; Anthropology; Ecology; Evolutionary Biology; Animal Systematics/Taxonomy/Biogeography.; Electronic books